Influence of Chronic Exposure to Cold Environment on Thyroid Gland Function in Rabbits - Mustafa, S.; Elgazzar, A. (Hormone and Metabolic Research, 2014)
Chronic exposure to cold can affect the thyroid gland. However, the effect on thyroid gland perfusion images and the ratio between thyroid hormones secretion were not addressed in any previous study. The present study investigates the effects of chronic cold exposure on thyroid gland function using radionuclide tracer and thyroid hormones secretion concentration. New Zealand white rabbits weighing approximately 1.8–2 kg were kept in a cold room (4°C) for 7 weeks. Thyroid scintigraphy was performed for cold exposed rabbits and a control rabbit group. Each rabbit was injected with 115 MBq (3.1 mCi) technetium-99m pertechnetate (99mTc pertechnetate). Studies were performed using Gamma camera equipped with a low energy, high resolution, pinhole collimator interfaced with a computer. Static images were acquired 20 min after administration of the radiotracer. Rabbits chronically exposed to cold had less body weights than control. Thyroid gland uptake is higher in rabbits chronically exposed to cold than controls using radionuclide perfusion study. The increase was proportional to the time period, so the increase after 7 weeks was greater than 5 weeks. There is also an increase in free triiodothyronine (FT3) and a decrease in free thyroxine (FT4) values. Our results indicate that thyroid gland uptake is higher in rabbits chronically exposed to cold than control and the increase was proportional to the duration. The decrease in rabbit body weights may be related to the increase in metabolism due to the increase of thyroid hormones. Chronic cold exposure also increased the conversion of T4 to T3, which is more potent in thermogenic effect.
Keywords: cold; perfusion; thyroid; rabbit; thyroxine (T4); triiodothyronine (T3); radionuclide; 99mTc pertechnetate